Characteristics of Heart Failure Patients based on Its Causes in Camelia Hospitalization Room Dr. Soetomo General Hospital Surabaya January - December 2017 - Chronica Elsa Retta Lumban Tobing; Budi Baktijasa Dharmadjati; Heroe Soebroto (Faculty of Medicine Universitas Airlangga, 2020)
Introduction: Heart failure is one of cardiovascular diseases which becomes a global health problem, especially in Indonesia. It’s a clinical syndrome caused by variety of underlying diseases. Different causes that cause heart failure in patients will certainly lead to different manifestations and outcomes. Methods: This research was a descriptive study using secondary data taken from the patient's medical records. The number of samples in this study were 197 patients with heart failure in Camelia Hospitalization Room Dr. Soetomo General Hospital Surabaya. Sampling technique was total sampling. The variables were age, sex, stage, symptoms, physical examination, and pharmacological treatment. The data were analyzed descriptively. Results: Most heart failure causes in this hospital was coronary heart disease (40.6%). Patients aged 46-65 years old and male patients were more dominant although the difference was not really significant. Male patients were dominant in heart failure due to coronary heart disease and hypertension, meanwhile female patients were dominant in heart valve disease and other causes. Most patients in all causes of heart failure were diagnosed at advanced stage, such as stage III (35.5%) and stage IV (35.5%). Main symptom that was found more in the patients was dyspnea (70.1%), which could be found in coronary & heart valve disease. Physical examination results were based on the causes. Most pharmacological treatments that the patients had were Furosemide (88.3%) and Spironolactone (73.6%). Conclusion: Coronary heart disease still becomes the main cause of heart failure. Heart failure was more common in early and late elderly (46-65 years old), with male patients were more dominant. More patients were diagnosed at advanced stage. Symptom that was found more was dyspnea. Physical examination results were various based on its causes. Pharmacological treatments that the patients had gotten were Furosemide, kind of diuretics, and Spironolactone, kind of aldosterone antagonist.